(untitled) - Farooq, Shazia (Netherlands, 2017)
During the last decades, fluorescence spectroscopy has emerged as a powerful tool in the fields of biophysics, biotechnology, biochemistry, cellular biology and the medical sciences. These techniques are highly sensitive, and allow us to study the structure and dynamics of (bio)molecular systems (Valeur 2001). A significant advantage of fluorescence techniques is that they can often be non-invasive and measurements can be performed in real time. In this thesis different advanced fluorescence methods will be used to study two important biological processes: (1) DNA dynamics and (2) plant photosynthesis. The first part aims at improving the smFRET technique for the analysis of DNA dynamics and other fast conformational changes. This improvement is made by combining and developing instrumentation and data evaluation tools. The second part is the continuous development of time-resolved fluorescence spectroscopy methods, as well their application in the field of photosynthesis to study ultrafast processes in thylakoid membranes and leaves. The two fluorescence techniques are technically and conceptually very different, but they are both designed for analysis of biomolecular systems. In this thesis, the techniques are applied to study energy transfer and dynamical changes in DNAs, thylakoid membranes and leaves.
Keywords: DNA,DNA; Phân tích,Analysis